Correspondence - Richardson, Henry Handel, 1870-1946.; Price, Harry, 1881-1948.; Purdie, Edna, 1894-; Kaye, Lucie (1928)
Letters written by Henry Handel Richardson to Professor E. Purdie, Miss Lucie Daye (who was the Secretary of the National Laboratory of Physical Research) and Mr Harry Price. The letters to Purdie were signed "H.H.R.", but the letters to Kaye and Price were signed "Ethel F. L. Robertson". Some of the letters were from Harry Price to Mrs Robertson.
Manuscript reference no. : NLA MS 7870.
Photocopies.
Originals held by Royal Holloway and Bedford New College , University of London and Harry Price Library, University of London Library.
Novelist. See 'The Oxford companion to Australian literature', pp. 584-587.
Keywords: Richardson, Henry Handel, -- 1870-1946 -- Correspondence; Purdie, Edna, -- 1894- -- Correspondence; Kaye, Lucie, -- Correspondence; Price, Harry, -- 1881-1948 -- Correspondence; Novelists, Australian -- Correspondence; Authors, Australian -- Correspondence; Novelists; Authors